An important call: Suggestion of using IL-10 as therapeutic agent for COVID-19 with ARDS and other complications - Li-Jane Shih; Chun-Chun Yang; Min-Tser Liao; Kuo-Cheng Lu; Wan-Chung Hu; Chih-Pei Lin (Virulence)
The global coronavirus disease 2019 (COVID-19) pandemic has a detrimental impact on public health. COVID-19 usually manifests as pneumonia, which can progress into acute respiratory distress syndrome (ARDS) related to uncontrolled TH17 immune reaction. Currently, there is no effective therapeutic agent to manage COVID-19 with complications. The currently available anti-viral drug remdesivir has an effectiveness of 30% in SARS-CoV-2–induced severe complications. Thus, there is a need to identify effective agents to treat COVID-19 and the associated acute lung injury and other complications. The host immunological pathway against this virus typically involves the THαβ immune response. THαβ immunity is triggered by type 1 interferon and interleukin-27 (IL-27), and the main effector cells of the THαβ immune response are IL10-CD4 T cells, CD8 T cells, NK cells, and IgG1-producing B cells. In particular, IL-10 exerts a potent immunomodulatory or anti-inflammatory effect and is an anti-fibrotic agent for pulmonary fibrosis. Concurrently, IL-10 can ameliorate acute lung injury or ARDS, especially those caused by viruses. Owing to its anti-viral activity and anti-pro-inflammatory effects, in this review, IL-10 is suggested as a possible treatment agent for COVID-19.